Number of Synergies Is Dependent on Spasticity and Gait Kinetics in Children With Cerebral Palsy. Issue 1 (January 2018) - Hashiguchi, Yu; Ohata, Koji; Osako, Sayuri; Kitatani, Ryosuke; Aga, Yumi; Masaki, Mitsuhiro; Yamada, Shigehito
Abstract : Purpose: Children with cerebral palsy have motor dysfunctions, which are mainly associated with the loss of motor coordination. For the assessment of motor coordination, muscle synergies calculated by nonnegative matrix factorization have been investigated. However, the characteristics of muscle synergies in children with cerebral palsy are not understood. Methods: This study compared the number of muscle synergies during gait between children with cerebral palsy and children with typical development and clarified whether certain clinical parameters differed according to the number of synergies. Results: Children with cerebral palsy had significantly fewer synergies than children developing typically. The extent of spasticity and gait kinetics differed according to the number of synergies. Conclusion: Increases in the number of synergies are limited by severe spasticity. The muscle synergies calculated by nonnegative matrix factorization have the potential to enable the quantification of motor coordination during gait. Abstract : This study compared the number of muscle synergies during gait between children with cerebral palsy and children with typical development and clarified whether certain clinical parameters differed according to the number of synergies in children with cerebral palsy.